Virgin Coconut Oil (VCO) Attenuates Hepatotoxicity Induced by Cigarette Smoke in Rats - Lilis T.; Saharnauli Janna verawaty Simorangkir; Okto P.E. Marpaung (Majalah Obat Tradisional, 2023)
Researchers have connected the antioxidants in virgin coconut oil (VCO) to the growing health benefits; however, little is known about the hepatoprotective and antioxidant properties of VCO against oxidative stress and liver damage brought on by smoking cigarettes. The research examined the hepatoprotective and antioxidant properties of VCO against oxidative stress and liver damage. Male Wistar rats were split into 4 groups: Group 1 (the control group) was fed rat pellets; Group 2 (the control positive group) was fed the basic diet and exposed to cigarette smoke; Group 3 was fed the basic diet and 0,45 ml VCO; Group 4 was provided the basic diet and 0,9 ml VCO. Serum liver biomarker (SGPT and SGOT) assays were performed after 28 days of therapy. When compared to the control group, exposure to cigarette smoke caused a substantial increase in blood liver enzymes. Treatment with VCO significantly prevented an increase of SGPT and SGOT levels compared to control positive group P2. This study demonstrated that inhaling cigarette smoke damages the liver and established the hepatoprotective properties of VCO against cigarette smoke-induced liver damage via reducing oxidative stress.